Innovative Construction Techniques Used At North Shore Construction Project - Kanchan K. Sen (Deep Foundations Institute, 2010)
The North Shore Connector (NSC) project will extend the Allegheny County Port Authority?s Light Rail Transit System from downtown Pittsburgh below the Allegheny River to the North Shore via twin bore tunnels. Jet grouting, diaphragm walls, and soil mixing were selected as cost-effective technically viable ground improvement and support of excavation techniques. Jet grouting was specified to provide break-out (egress) and break-in (ingress) block sections at the tunnel boring machine (TBM) launching and receiving pits. Jet grout treatment was also used adjacent to buildings with shallow foundations and below retaining walls along the tunnel alignment. A new method for measuring jet grout column diameter based on electrical resistivity was employed on the project. New equipment was introduced in the U.S for constructing soil mix temporary support of excavation using a soil-mix technique termed Cutter Soil Mixing (CSM) due to the use of two vertical cutting wheels that have evolved from diaphragm wall trench cutter technology. The system allows for continuous water tight soil mix panel construction including steel beams. This paper highlights some applications of jet grouting and various support of excavation systems (e.g. slurry walls, cement bentonite walls and CSM walls), including new innovative techniques (e.g. Cyljet and CSM) used under the constraints of an urban environment.